Opening clauses in collective bargaining agreements: More flexibility to save jobs? - Tobias Brändle; Wolf Dieter Heinbach (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
Collective bargaining agreements have been said to decrease deployment since the work of Calmfors and Driffill (1988). We investigate empirically whether opening clauses, flexible elements that have been introduced to reduce the decline in coverage, can indeed minimise this effect and increase job growth in covered firms. Using representative data on German establishments, the IAB Establishment Panel, in combination with data on opening clauses from the IAW, and performing propensity score matching to control for selectivity bias, we find that the existence of opening clauses has significantly negative effects on job destruction rates and that it increases job growth by approximately 0.73% per year. However, it does not seem the case that firms with explicit knowledge of opening clauses anticipate their increased flexibility, since they do not have higher job creation rates. As regards the actual application of opening clauses, our results do not show additional effects.
Keywords: J51; J63; C21; 330; Collective bargaining; opening clauses; job flows; propensity score matching; Tarifpolitik; Deregulierung; Arbeitsmarktflexibilität; Wirkungsanalyse; Beschäftigungseffekt; Arbeitsplatzsicherung; Deutschland